BER Assessment of FBMC Systems Augmented with Different Space-Time Coding Schemes Over Diverse Channels - Kaur, Satwinder; Kansal, Lavish; Singh Gaba, Gurjot; A. M. Al-Ja'afari, Mohannad (International Journal of Engineering and Technology, 2018)
Diverse methodologies of encoding schemes like space-time block codes (STBC), orthogonal space-time block codes (OSTBC) &quasi-orthogonal space-time block codes (QOSTBC) are being proposed as alternatives of basic Alamouti space-time encoding scheme for multiple input multiple output (MIMO) scheme for existing wireless communication systems. Since filter bank multi-carrier (FBMC) scheme is an integral part of the 5th generation (5G) cellular systems, the performance of these schemes needs to be investigated for FBMC methodology also. Alamouti and Space-time block codes are widely used in MIMO system because of their ability to achieve full diversity and the different channels are used at the receiver. In this work, we proposed different approaches for the bit error rate (BER) of Alamouti, STBC3, and STBC4 in FBMC. These approaches are based on the type of space-time encoding and number of receiving antennas being used for each space time encoding scheme for analyzing the MIMO-FBMC. Moreover, we also investigation the performance of these proposed MIMO schemes over Rayleigh and additive white Gaussian noise (AWGN) channel and compared it with the performance of BER or signal to noise ratio (SNR) of different channels.